Effects of telbivudine and entecavir for HBeAg-positive chronic hepatitis B: A meta-analysis - Su, Qi-Min (Baishideng Publishing Group Co., Limited, 2012)
AIM: To compare the effects of telbivudine (LDT) and entecavir (ETV) in treatment of hepatitis B e antigen (HBeAg)-positive chronic hepatitis B by meta-analysis. METHODS: We conducted a literature search using PubMed, MEDLINE, EMBASE, the China National Knowledge Infrastructure, the VIP database, the Wanfang database and the Cochrane Controlled Trial Register for all relevant articles published before April 1, 2012. Randomized controlled trials (RCTs) comparing LDT with ETV for treatment of HBeAg-positive chronic hepatitis B were included. The data was analyzed with Review Manager Software 5.0. We used relative risk (RR) as an effect measure, and reported its 95% CI. Meta-analysis was performed using either a fixed-effect or random-effect model, based on the absence or presence of significant heterogeneity. Two reviewers assessed the risk of bias and extracted data independently and in duplicate. The analysis was executed using the main outcome parameters including hepatitis B virus (HBV) DNA undetectability, alanine aminotransferase (ALT) normalization, HBeAg loss, HBeAg seroconversion, drug-resistance, and adverse reactions. Meta-analysis of the included trials and subgroup analyses were conducted to examine the association between pre-specified characteristics with the therapeutic effects of the two agents. RESULTS: Thirteen eligible trials (3925 patients in total) were included and evaluated for methodological quality and heterogeneity. In various treatment durations of 4 wk, 8 wk, 12 wk, 24 wk, 36 wk, 48 wk, 52 wk, 60 wk and 72 wk, the rates of HBV DNA undetectability and ALT normalization in the two groups were similar, without statistical significance. At 4 wk and 8 wk of the treatment, no statistical differences were found in the rate of HBeAg loss between the two groups, while the rate in the LDT group was higher than in the ETV group at 12 wk, 24 wk, 48 wk and 52 wk, respectively (RR 2.28, 95% CI 1.16, 7.03, P = 0.02; RR 1.45, 95% CI 1.16, 1.82, P = 0.001; RR 1.45, 95% CI 1.11, 1.89, P = 0.006; and RR 1.86, 95% CI 1.04, 3.32, P = 0.04). At 4 wk, 8 wk, 60 wk and 72 wk of the treatment, there were no significant differences in the rate of HBeAg seroconversion between the two groups, while at 12 wk, 24 wk, 48 wk and 52 wk, the rate in the LDT group was higher than in the ETV group (RR 2.10, 95% CI 1.36, 3.24, P = 0.0008; RR 1.71, 95% CI 1.29, 2.28, P = 0.0002; RR 1.86, 95% CI 1.36, 2.54, P < 0.0001; and RR 1.87, 95% CI 1.21, 2.90, P = 0.005). The rate of drug-resistance was higher in the LDT group than in the ETV group (RR 3.76, 95% CI 1.28, 11.01, P = 0.02). In addition, no severe adverse drug reactions were observed in the two groups. And the rate of increased creatine kinase in the LDT group was higher than in the ETV group (RR 5.58, 95% CI 2.22, 13.98, P = 0.0002). CONCLUSION: LDT and ETV have similar virological and biomedical responses, and both are safe and well tolerated. However, LDT has better serological response and higher drug-resistance.